2002
DOI: 10.1128/mmbr.66.2.179-202.2002
|View full text |Cite
|
Sign up to set email alerts
|

T Antigens of Simian Virus 40: Molecular Chaperones for Viral Replication and Tumorigenesis

Abstract: Simian virus 40 (SV40) is a small DNA tumor virus that has been extensively characterized due to its relatively simple genetic organization and the ease with which its genome is manipulated. The large and small tumor antigens (T antigens) are the major regulatory proteins encoded by SV40. Large T antigen is responsible for both viral and cellular transcriptional regulation, virion assembly, viral DNA replication, and alteration of the cell cycle. Deciphering how a single protein can perform such numerous and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
228
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(239 citation statements)
references
References 275 publications
1
228
1
1
Order By: Relevance
“…The ability of the J domain to associate with domain II raises new and interesting questions about whether the J domain function of Tag may remodel protein-protein interactions that involve domain IIa and IIb, akin to those involving retinoblastoma-related proteins (32,33). Among the potential candidates for remodeling by the J domain are p53, DNA polymerase ␣-primase, RPA, and transcription factors (1)(2)(3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of the J domain to associate with domain II raises new and interesting questions about whether the J domain function of Tag may remodel protein-protein interactions that involve domain IIa and IIb, akin to those involving retinoblastoma-related proteins (32,33). Among the potential candidates for remodeling by the J domain are p53, DNA polymerase ␣-primase, RPA, and transcription factors (1)(2)(3).…”
Section: Discussionmentioning
confidence: 99%
“…7B, dotted line) (32,33). The nuclear localization signal of Tag and a cluster of phosphorylation sites that modulate interactions between Tag hexamers to promote bidirectional DNA unwinding during viral replication are also located in the C-terminal region of domain I (1-3, 5, 6).…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal region of T-antigen is also required for this interaction and this region is known as the J-domain because of its homology to DnaJ and it confers a molecular chaperone function to T-antigen (see Sullivan and Pipas (2002) for an excellent review). Reintroducing a LXCXE domain to an N-terminally truncated T-antigen confers on cells the ability to grow to high density (Tevethia et al, 1997).…”
Section: Interaction Of Sv40 Large T-antigen With Prb and Its Family mentioning
confidence: 99%
“…[9][10][11][12]. The ability of T antigen to cause karyotypic instability in human cells has been found to correlate with its ability to deregulate normal mitotic checkpoints, but the exact mechanism is not known.…”
Section: Introductionmentioning
confidence: 99%
“…(reviewed in refs. [9][10][11][12]. A recent report on yeast twohybridization and immunoprecipitation techniques showed that the Bub1 gene is another targeting protein of SV40 Tag (9).…”
Section: Introductionmentioning
confidence: 99%